Fecal microbiota relationships with childhood obesity: A scoping comprehensive review. (15th December 2021) - de Cuevillas, Begoña; Milagro, Fermín I.; Tur, Josep A.; Gil‐Campos, Mercedes; de Miguel‐Etayo, Pilar; Martínez, J. Alfredo; Navas‐Carretero, Santiago
Summary: Childhood obesity is a costly burden in most regions with relevant and adverse long‐term health consequences in adult life. Several studies have associated excessive body weight with a specific profile of gut microbiota. Different factors related to fecal microorganism abundance seem to contribute to childhood obesity, such as gestational weight gain, perinatal diet, antibiotic administration to the mother and/or child, birth delivery, and feeding patterns, among others. This review reports and discusses diverse factors that affect the infant intestinal microbiota with putative or possible implications on the increase of the obesity childhood rates as well as microbiota shifts associated with excessive body weight in children.